KUALITAS PANCAKE DENGAN SUBSTITUSI TEPUNG TEMPE KACANG TUNGGAK DAN TEPUNG UBI JALAR UNGU - Leonard, Patricia; Pranata, Franciscus Sinung; Swasti, Yuliana Reni (Pro Food, 2023)
Pancakes are a snack and alternative food for breakfast which are made by grilling on a pan. The use of cowpea tempe flour and purple sweet potato flour is to reduce the use of wheat flour in Indonesia and to increase the protein and fiber content in pancake. The aim of the research was to find out the right formulation to produce the best quality pancakse and to find out the effect on pancakes based on chemical, physical, microbiological and organoleptic qualities. This research used a completely randomized design with three repetitions for each treatment, namely 100:0:0 (K), 50:50:0 (A), 50:25:25 (B), dan 50:0:50 (C). The results showed that pancakes contained 31.45-35.41% moisture content, 1.64-2.06% ash content, 4.88-10.04% protein content, 7.39-9.15% fat content, carbohydrate content 45.31-52.00%, insoluble fiber content 2.72-6.29%, soluble fiber content 1.92-5.97%, hardness 3.76-5.13 N, springiness 0.11-0.50, swelling power 152.48-161.91%, yellowish orange color, total plate count 0-5,33 x 10¹ CFU/g, and yeast mold rate 0 CFU/g. Pancakes with substitution of cowpea tempe flour and purple sweet potato flour which have the best quality are pancakes treatment 50:50:0 (A) based on chemical, physical and microbiological parameters.